2001
DOI: 10.1002/hed.1136
|View full text |Cite
|
Sign up to set email alerts
|

Serial positron emission tomography scans following radiation therapy of patients with head and neck cancer

Abstract: PET is useful for initial imaging of head and neck cancers. SUV does not appear to be useful for predicting outcome following treatment with RT. One-month post-RT scans were inaccurate for predicting the presence of cancer. Four-month post-RT scans were a better predictor for the presence of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(141 citation statements)
references
References 12 publications
6
132
2
1
Order By: Relevance
“…Allal et al [7] and Roh et al [8] found that high FDG uptake correlated with advanced pT and pN stages. However, in several studies, the SUV max of primary tumor or all lesions, including regional metastatic lymph nodes, was not confirmed as a significant factor predicting clinical outcome in the patients with HNSCC undergoing radiation therapy with or without chemotherapy [11][12][13][26][27][28]. In our results, the lower The pT stage is defined as the extent of primary tumor in terms of size and invasion into the adjacent structure.…”
Section: Discussioncontrasting
confidence: 78%
“…Allal et al [7] and Roh et al [8] found that high FDG uptake correlated with advanced pT and pN stages. However, in several studies, the SUV max of primary tumor or all lesions, including regional metastatic lymph nodes, was not confirmed as a significant factor predicting clinical outcome in the patients with HNSCC undergoing radiation therapy with or without chemotherapy [11][12][13][26][27][28]. In our results, the lower The pT stage is defined as the extent of primary tumor in terms of size and invasion into the adjacent structure.…”
Section: Discussioncontrasting
confidence: 78%
“…However, the range of cutoff values adopted in published studies to define patients at high or low risk of events markedly varied between 3.7 and 9 g/ml (median: 5.8). Noteworthy, also 2 negative studies are available in the literature (Ashamalla et al, 2014;Greven et al, 2001). In (Greven et al, 2001), patients with local recurrence had a mean pretreatment SUV Max of 7.7 g/ml versus 8.2 g/ml for patients without local recurrence.…”
Section: Suvmax and Metabolic Tumor Volumementioning
confidence: 99%
“…Noteworthy, also 2 negative studies are available in the literature (Ashamalla et al, 2014;Greven et al, 2001). In (Greven et al, 2001), patients with local recurrence had a mean pretreatment SUV Max of 7.7 g/ml versus 8.2 g/ml for patients without local recurrence. In (Ashamalla et al, 2014), SUVMax was correlated with OS in univariate analysis, but not in multivariate analysis.…”
Section: Suvmax and Metabolic Tumor Volumementioning
confidence: 99%
“…For example, radiotherapyinduced changes may be seen as fluorodesoxyglucose-avid lesions on positron emission tomography scanning up to 6 months or more after treatment. These are a well known false-positive results on follow-up exams after head and neck, rectal, and lung tumors [18][19][20][21]. An inflammatory wound has, by definition, not completed the healing process and is probably more at risk of complication under antiangiogenic treatment.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%